Higher Order Commutators of Fractional Integral Operator on the Homogeneous Herz Spaces with Variable Exponent - Liwei Wang; Meng Qu; Lisheng Shu (Journal of Function Spaces and Applications)
By decomposing functions, we establish estimates for higher order commutators generated by fractional integral with BMO functions or the Lipschitz functions on the homogeneous Herz spaces with variable exponent. These estimates extend some known results in the literatures.